(untitled) (Research, Society and Development, 2021)
Tomato is a highly perishable fruit due to its large amount of water, in addition to being very affected by post-harvest problems. One of the alternatives to reduce losses and waste is processing through drying, which makes perishables more stable, in addition to being able to use products, such as substandard tomatoes, for the fresh market. The objective was to evaluate the influence of different temperatures (combination of 100/65 °C; 85 °C, 75 °C; 65 °C) and types of cut (4 and 8 slices) on the drying kinetics and on the quality of tomato powder. The drying process was evaluated in relation to the rate of drying and loss of mass over time, and the yield was finally quantified. The quality of the powder obtained was evaluated by means of particle size, color, total soluble solids content (°Brix), pH and solubility. Tomato drying at a temperature of 100/65 °C, sliced ​​into 8 parts, took place in less time. The yield of tomato powder was on average 5.82%. The powder obtained from tomato cut into 8 slices had a finer granulometry, regardless of the drying temperature. The drying temperature at 65 °C resulted in powder with less darkening in color. On the other hand, tomato powder dried at 75 ºC had the highest amount of °Brix, and those obtained at temperatures 100/65 and 65 °C, cut into 4 slices, had the higher pH. In all treatments performed, high solubility was obtained, above 99%.